Etnografi Komunikasi dalam Pembelajaran Bahasa Indonesia di SMP Darussalam Cimanggu - Dwi Setiawan; Lutfi Eskawati; Diana Diana (Jurnal Pengabdian Masyarakat Nusantara, 2022)
This article discusses the application of communication ethnography in Indonesian language learning at Darussalam Cimanggu Middle School. This research aims to explore how an ethnographic communication approach can enrich the Indonesian language teaching and learning process. The methods used include observation, interviews and document analysis. The research results show that this approach can increase student engagement and understanding of the social and cultural context in language use.